POSTPARTUM CARE CENTER KOTA BANJARMASIN - Putri Anisa; Dila Nadya Andini (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
The postpartum period is a crucial phase for mothers. During this time, most mothers undergo significant physical and psychological changes, such as Postpartum Depression (PPD) or what is commonly known as the baby blues, making this phase one of the main contributing factors to the high Maternal Mortality Rate (MMR). The lack of dedicated facilities and services for postpartum mothers highlights the urgency of designing a Postpartum Care Center in Banjarmasin as a solution to provide a supportive environment for maternal recovery. This design applies the Spatial Perception method and the Therapeutic Architecture approach to create spaces that promote healing. The implementation of the Mommy’s Therapeutic Space concept in the Postpartum Care Center is expected to offer a safe, comfortable, and responsive environment for postpartum recovery. Mommy’s Therapeutic Space integrates four key aspects: Social Connectivity, which fosters social interaction among mothers; Homelike Comfort, which provides a sense of security, tranquility, and comfort akin to home; Serenity, which promotes relaxation and peace of mind; and Maternal Essence, which prioritizes maternal experiences and characteristics in design aspects. These four interconnected concepts are designed to create a Postpartum Care Center environment that not only supports the mother's recovery process but also contributes to long-term maternal well-being